Structural investigation of the capsular polysaccharide from a clinical isolate of Fusobacterium necrophorum subspecies necrophorum biotype a strain LA 81–617. (January 2020) - Vinogradov, Evgeny; Altman, Eleonora
Abstract: A capsular polysaccharide (CPS) from Fusobacterium necrophorum subspecies necrophorum biotype A strain LA 81–617 was isolated from a saline cell wash and purified by gel and anion-exchange chromatography. The structure of the CPS was studied by one- and two-dimensional 1 H and 13 C NMR spectroscopy techniques in combination with electrospray ionization mass spectrometry (ESI-MS). The CPS was found to resemble the bacterial cell-wall murein polysaccharide backbone, consisting of N -acetylglucosamine and N -acetylmuramic acid (MurNAc) components, with the following structure:-[-4-β-MurNAc-4-β-GlcNAc-]n -with N-acetyl-1, 6-anhydro-β-muramic acid at the reducing end. This is the first report on the structure of F. necrophorum capsular polysaccharide. Graphical abstract: Image 1 Highlights: Capsule of F. necrophorum biotype A strain LA 81–617 consists of peptidoglycan fragments. Peptidoglycan fragments are probably produced by the mechanism of peptidoglycan recycling. No similar capsule was found in several F. nucleatum strains.